2023
DOI: 10.3390/jpm13060914
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Circulating lncRNA H19 in Ankylosing Spondylitis Patients and Its Correlation with Disease Activity

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease that results in severe pain and stiffness in the joints. The causes and pathophysiology of AS are still largely unknown. The lncRNA H19 plays key roles in the pathogenesis of AS by mediating inflammatory progression by acting in the axis of IL-17A/IL-23. The aims of this study were determining the role of lncRNA H19 in AS and assessing its clinical correlation. A case–control study was conducted and qRT-PCR was utilized to measure H19 expression. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…In a study conducted by Zhang et al, it was observed that the lncRNA H19 exhibited a significant upregulation in AS patients compared to healthy controls ( Zhang et al, 2020 ). This finding was further corroborated by another study conducted by Marwa M. Esawy et al ( Esawy et al, 2023 ). In the experiment conducted by Zhang et al, the knockdown of H19 downregulated vitamin D receptor (VDR) and miR-675-5p expressions while promoting miR-22-5p expression in peripheral blood mononuclear cells (PBMCs).…”
Section: Lncrnas Involved In the Pathogenesis Of Assupporting
confidence: 82%
“…In a study conducted by Zhang et al, it was observed that the lncRNA H19 exhibited a significant upregulation in AS patients compared to healthy controls ( Zhang et al, 2020 ). This finding was further corroborated by another study conducted by Marwa M. Esawy et al ( Esawy et al, 2023 ). In the experiment conducted by Zhang et al, the knockdown of H19 downregulated vitamin D receptor (VDR) and miR-675-5p expressions while promoting miR-22-5p expression in peripheral blood mononuclear cells (PBMCs).…”
Section: Lncrnas Involved In the Pathogenesis Of Assupporting
confidence: 82%